SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Complex life histories predispose aphids to recent abundance declines - Michael S. Crossley; Olivia M. Smith; Thomas S. Davis; Sanford D. Eigenbrode; Glen L. Hartman; Doris Lagos‐Kutz; Susan E. Halbert; David J. Voegtlin; Matthew D. Moran; William E. Snyder (Global Change Biology, 2021)
Many animals change feeding habits as they progress through life stages, exploiting resources that vary in space and time. However, complex life histories may bring new risks if rapid environmental change disrupts the timing of these switches. Here, we use abundance times series for a diverse group of herbivorous insects, aphids, to search for trait and environmental characteristics associated with declines. Our meta dataset spanned three world regions and >300 aphid species, tracked at 75 individual sites for 10–50 years. Abundances were generally falling, with median changes of −8.3%, −5.6%, and −0.1% per year in the central USA, northwestern USA, and United Kingdom, respectively. Aphids that obligately alternated between host plants annually and those that were agricultural pests exhibited the steepest declines, relative to species able to persist on the same host plant year‐round or those in natural areas. This suggests that host alternation might expose aphids to climate‐induced phenology mismatches with one or more of their host plant species, with additional risks from exposure to insecticides and other management efforts. Warming temperatures through time were associated with milder aphid declines or even abundance increases, particularly at higher latitudes. Altogether, while a warming world appeared to benefit some aphid species in some places, most aphid species that had time‐sensitive movements among multiple host plants seemed to face greater risk of decline. More generally, this suggests that recent human‐induced rapid environmental change is rebalancing the risks and rewards associated with complex life histories.

First occurrence of Diaphorina citri in East Africa, characterization of the Ca. Liberibacter species causing huanglongbing (HLB) in Tanzania, and potential further spread of D. citri and HLB in Africa and Europe - Mpoki M. Shimwela; Hossein A. Narouei-Khandan; Susan E. Halbert; Manjunath L. Keremane; Gerald V. Minsavage; Sujan Timilsina; Deogracious Protas Massawe; Jeffrey B. Jones; Ariena H. C. van Bruggen (European Journal of Plant Pathology, 2016)

Global climate suitability of citrus huanglongbing and its vector, the Asian citrus psyllid, using two correlative species distribution modeling approaches, with emphasis on the USA - Hossein A. Narouei-Khandan; Susan E. Halbert; Susan P. Worner; Ariena H. C. van Bruggen (European Journal of Plant Pathology, 2016)

First record of Calophya schini (Hemiptera: Calophyidae) in Ethiopia and Kenya - William A. Overholt; Robert S. Copeland; Susan E. Halbert (International Journal of Tropical Insect Science, 2013)

Potato Virus Y transmission efficiency for some common aphids in Idaho - Susan E. Halbert; Dennis L. Corsini; Monica A. Wiebe (American Journal of Potato Research, 2003)

Domyzus (nectarosiphon) species other thanm persicae pose a threat to the idaho potato crop? - Susan E. Halbert; Steven J. Castle; Thomas M. Mowry (American Journal of Potato Research, 1995)